Jaya Tuition Centre - Hussin, Siti Rahayu; Hashim, Haslinda; Wang, Yaw Siong (Universiti Putra Malaysia Press, 2013)
This case revolves around the business survival of Jaya Tuition Centre, Melaka (JTCMM), a franchisee of Jaya Tuition Centre (JTC). JTCMM has been showing poor performance compared to other JTC franchisees. The difficulties facing JTCMM are reflected by symptoms such as declining sales, customer complaints, and difficulties in retaining customers. The management had implemented several changes in the tuition centre such as offering an Exam-Based Tuition classes, Homework Guidance Service and Transportation Service. These changes helped to increase the number of students and generated higher revenues for JTCMM. However, compared to other JTC tuition franchisees, JTCMM had the lowest sales revenue. The management was faced with the challenge to redress the tuition centre’s situation by showing at least a 20% increase in sales revenue in the next six months. Areas of improvement that needed to be considered include: service positioning, service personnel competencies, service outlet environment, customer experience and augmented service.